1998
DOI: 10.1111/j.1471-6402.1998.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Sociocultural Norms

Abstract: Internalization of sociocultural norms about the body has been theorized to be an important factor in fostering body dissatisfaction in women. Some theorists have suggested that a lesbian identity may buffer or immunize lesbians from the damaging effects of society's pressure to be thin by reducing this internalization. This study was designed to test this claim empirically. Questionnaires were completed by 108 lesbians and 115 heterosexual women recruited through snowball sampling. Lesbians felt more fit, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(12 citation statements)
references
References 27 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…Other studies show that the importance of internalization is not limited to African American women (Bergeron & Senn, 1998;Durkin & Paxton, 2002;Field et al, 2001;Halliwell & Dittmar, 2004;Morry & Staska, 2001). For example, Halliwell and Dittmar (2004) found, in a nonstudent female sample, that comparisons to thin models increased anxiety among high-internalization participants, but had no significant effect on low-internalization participants.…”
Section: Internalization Of the Feminine Idealmentioning
confidence: 98%
“…Other studies show that the importance of internalization is not limited to African American women (Bergeron & Senn, 1998;Durkin & Paxton, 2002;Field et al, 2001;Halliwell & Dittmar, 2004;Morry & Staska, 2001). For example, Halliwell and Dittmar (2004) found, in a nonstudent female sample, that comparisons to thin models increased anxiety among high-internalization participants, but had no significant effect on low-internalization participants.…”
Section: Internalization Of the Feminine Idealmentioning
confidence: 98%
“…The other unique theme is that, although there was a general agreement in this sample that lesbians are more accepting of all weights and body shapes than in the heterosexual community (Bergeron & Senn 1998, Swami & Tovee 2006), there is also concern about the impact of this acceptance on health. This study was consistent with others that found lesbians receptive to interventions that focused on health, healthy behaviours and fitness, rather than on weight, BMI and being thin (Bowen et al.…”
Section: Discussionmentioning
confidence: 86%
“…Lesbians have been found to have attitudes similar to heterosexual comparisons concerning weight, appearance and dieting and the same rates of bulimia in some studies (Brand et al. 1992, Heffernan 1996, Feldman & Meyer 2007), while others found that lesbians have less negative attitudes about their bodies (Bergeron & Senn 1998, Polimeni et al. 2009) and find women with higher BMIs more attractive (Swami & Tovee 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Several studies found that lesbians are more accepting of their bodies and more tolerant of higher weight in self and others (Bergeron & Senn, 1998;Gettelman & Thompson, 1993;French et al, 1996;Herzog, Newman, Yeh, & Warshaw, 1992;Maor, 2012;Markey & Markey, 2014;Morrison et al, 2004;Polimeni et al, 2009;Siever, 1994;Swami & Tovee, 2006). However, other studies found lesbians to be similar to heterosexual women in concerns about weight, appearance, body acceptance, and/or dieting (Brand et al, 1992;Davids & Green, 2011;Feldman & Meyer, 2007;Heffernan, 1996;Keridwen, 2012;Huxley, Clark, & Halliwell, 2012;Kozee & Tylka, 2006;Peplau et al, 2009).…”
Section: Lesbian Community Norms About Weightmentioning
confidence: 99%